Islam kot nacionalistični instrument odpora proti percipirani dominaciji Zahoda - Potočnik, Dragan (Edinost in dialog, 2023)
In the 19th century, the Western colonial powers took over the Muslim world and implemented policies which were traumatic for ruled Muslims. Although Muslim countries gained formal independence in the middle of the 20 th century, the bulk of world's Muslims believes that the West still dominates their world through neo-colonialism. This perception has been particularly generated by military interventions of the Western powers. At first Muslims had tried to resist perceived Western domination through the secular Arab nationalism, however after 1967, Islam has assumed the role of nationalist instrument of resistance. The relations between the Muslim world and the West, especially radicalization of Muslims, can be explained by application of the sociological concepts of cultural defense, religious performance and cosmic war.
Keywords: islam; Muslim world; muslimanski svet; neo-colonialism; neokolonializem; radicalization; radikalizacija; religijski nacionalizem; religious nationalism; West; Zahod